2015
DOI: 10.4172/2329-6925.1000175
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Digit Ratio and Idiopathic Pulmonary Arterial Hypertension in Japanese Women

Abstract: Aim: Endothelin-1 (ET-1) is the key vasoactive mediator in patients with pulmonary arterial hypertension (PAH), and sex steroids are known to influence ET-1 levels. Additionally, the second to fourth digit (2D:4D) ratio is a biometric marker influenced by testosterone concentrations and androgen receptor sensitivity in the uterus, and some reports have linked (2D:4D) ratio to disease predisposition among patients with gender-dependent conditions. Since idiopathic PAH (IPAH) is more prevalent in women, we hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…The lack of significant associations in this study might indicate that 2D:4D is not a useful proxy for CVDs in women. This is in contrast to recent studies on 2D:4D and different cardiovascular‐related outcomes, including their causality of death (Asuku et al, 2019; Lenz & Kornhuber, 2018;Wang et al, 2018; Yamamoto et al, 2015). However, our study had one of the largest sample sizes up to date, and included a group of relatively homogenous women of white, European descent.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The lack of significant associations in this study might indicate that 2D:4D is not a useful proxy for CVDs in women. This is in contrast to recent studies on 2D:4D and different cardiovascular‐related outcomes, including their causality of death (Asuku et al, 2019; Lenz & Kornhuber, 2018;Wang et al, 2018; Yamamoto et al, 2015). However, our study had one of the largest sample sizes up to date, and included a group of relatively homogenous women of white, European descent.…”
Section: Discussioncontrasting
confidence: 81%
“…Negative correlation was observed between 2D:4D and adiponectin and HDL‐cholesterol, which is also relevant to CVD risk. A study among Japanese women have found a significantly higher 2D:4D in a group with idiopathic pulmonary hypertension compared to a control group (Yamamoto et al, 2015). A more recent cross‐national study on sex‐specific relation between 2D:4D and causes of mortality in 23 countries revealed that among women, 2D:4D is related to ischaemic heart disease as a cause of death (normalized to the national means) (Lenz & Kornhuber, 2018).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…So, during that period, if there are changes in the environment of the uterus (such as malnutrition or changes in the level of hormone within the uterus), not only will systems and organs structure of the fetus change, but also it affects ratio of fingers. Therefore, studying the ratio of fingers can indirectly indicate development of embryo during the fetal period in the uterus and the changes occurring in this period (Lu, et al, 2015;Yamamoto, Tamura, Ono, Takei, & Sano, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found 2D:4D to be associated with reproductive cancers 25,30,31 . As for general health characteristics, 2D:4D was associated with various cancers 32,33 , idiopathic pulmonary hypertension 34 and other morbidities such as systemic lupus erythematosus 35 , autism spectrum disorders 36 , and congenital adrenal hyperplasia 37,38 .…”
mentioning
confidence: 99%